A DISK MIRROR RECENTLY DISCOVERED SOUTH THE LOWER MUREȘ - Vitalie Bârcă (Journal of Ancient History and Archaeology, 2016)
The object of this study is the analysis of the disk mirror discovered in 2010 during the rescue archaeological excavations carried out in occasion of the construction of the Arad-Timişoara motorway, respectively the Arad-Seceani sector. The mirror was found at  ca. 1 m north grave 1 in site B0_6, where beside other two cremation graves, poorly preserved, other 129 archaeological features were also investigated. Though not exhaustively, we attempt herein to present the origin, distribution of this mirror type in the Sarmatian world and the chronological interval of their use within said environment. The author notes that these disk mirror types from the funerary Sarmatian features of the Great Hungarian Plain count amongst the most numerous, being found within funerary contexts on the entire duration of the Sarmatian inhabitancy of this geographical area. Further, the author notes that mirrors of the type are widely spread on broad geographical areas, hence the establishment of any production centres is highly difficult, but also that very likely, they were produced in various cultural environments over several centuries. Their high numbers in the Sarmatian world proves it is possible they made them, although there is no certain substantiating evidence. The author does not exclude either the possibility of the presence of travelling artisans in the Sarmatian environment making certain item categories upon order, mirrors of the type included. In terms of the dating of G 1 at Arad (site B_06), where the mirror most definitely originates, the author concludes that together with the other two graves (G 2 and G 3) are contemporary and date sometime to the end of the 2nd century – early decades of the 3rd century AD.